(untitled) (Journal of Partial Differential Equations, 2019)
We consider the existence and regularity of a weak solution to a class of systems containing a p-curl system in a multi-connected domain. This paper extends the result of the regularity theory for a class containing a p-curl system that is given in the author’s previous paper. The optimal C1+α-regularity of a weak solution is shown in a multi-connected domain.